Atypical cellular neurothekeoma: a case report with a novel NF1 mutation - Valli de la Guardia; Edgardo Castro-Pérez; Ana I. Porcell; Sara González de Tena-Dávila; Marina Pacheco (BMC, 2024)
Abstract Atypical cellular neurothekeoma is a rare benign soft-tissue tumour that usually arises in the head and neck region, shoulder girdles, and proximal extremities, predominantly in young women. This dermal neoplasm is under-reported in the literature and is not uncommonly misdiagnosed as a malignant tumour due to its worrisome histologic characteristics. Currently, the diagnosis of cellular neurothekeoma relies on a panel of non-specific immunohistochemical markers and its etiopathogenesis is unknown. Herein, we present the case of an atypical cellular neurothekeoma in the arm of a 49-year-old woman, describing its microscopic features and immunohistochemical profile. Additionally, we present a novel heterozygous predicted inactivating NF1 mutation, not previously reported, which was identified using high-throughput molecular techniques. Such finding might provide insights into the pathogenesis of neurothekeoma, potentially contributing to future refinements in diagnosis, which would enable more precise identification of this neoplasm.